The body in advertising and the consumers - Pereira, Francisco José Costa (2021)
Advertising is a mass communication, where, sometimes, beautiful people try to persuade consumers to buy or to do something, because our society places a very high premium on physical attractiveness and tends to assume that what is beautiful is good. In this away the physically attractive source functions as a cue that facilitates information processing by directing consumers' attention to relevant stimuli, which gives rise to positive feelings, (Solomon, Bamossy and Askegaard, 1999). The person's satisfaction with the physical image it presents to others is affected by the proximity that image corresponds to the image valued by his culture, because each culture develops their ideals of beauty that may include physical features as well as clothing styles, among others.